Differences in exposure and altitudinal limits as climatic indicators in a profile from Western Himalaya to Tian Shan - Richter, Michael; Pfeifer, Hartmut; Fickert, Thomas (ERDKUNDE, 1999)
Five mountain ranges were chosen for a numerical determination of exposure differences for vegetation as well as for the determination of altitudinal limits of periglacial land forms. A meridional transect crosses parts of High Asia between 43 and 34°N, including the Turgen Valley in the Sailijskij Alatau (Northern Tian Shan), Kuilju Valley in the Kuiljutau (Arpatakyr Plateau between Southern and Central Tian Shan), Oytagh Valley at Kara-Bahtiyar (Western Kunlun), Chaprot Valley in the Western Karakoram and Kaghan Valley located at the southern slopes of North-Western Himalaya. This sequence corresponds with the continental-oceanic change with summer precipitation in the north and central areas and winter and summer precipitation in the south. A brief summary of the results of this investigation follows: The comparison of differences in exposure and altitudinal belts in the study area improves knowledge mainly in the less known Oytagh, Arpatakyr and Sailijskij Alatau.No major floristic relationship between the different mountain ranges was found. There is a distinct border between Karakoram and Western Kunlun that differentiates the Tibet-Himalaya complex from the Tian Shan complex. A distinct transmission of maximum exposure contrasts is present in all five mountain ranges. It shows the semi-arid transition, found in the medium altitudes of the dry mountains and in the lower altitudes of the moist mountains. The application of the similarity analysis is a new approach of plant geography to enable climatological interpretation in semi-arid to semi-humid mountains. The climatic-ecological view leads to estimations concerning the genesis of regional air streams and of humidity patterns. The latter can be used to explain the lack or presence of certain altitudinal belts, e.g. of dark forests in the western Kunlun. The Karakoram and parts of the western Kunlun, the mountains with the driest foothills, are defined by a high precipitation gradient. The equalization of humidity in the high belts leads to a floristic similarity between the alpine belts of all mountain ranges. The altitudinal differentiation indicates a distinct change of humidity from the arid centre with its elevated position of vegetation-belts, as well as of solifluidal forms to the more humid borders with its depression of corresponding belts. However, some mountain areas in the arid centre show remarkable small-scaled differences in precipitation.